The importance of considering debt and young children in activation: A survival analysis of return to welfare - NG, Irene N. Y. (Institutional Knowledge at Singapore Management University, 2023)
While there has been much research on welfare exit and entry into employment, less research has looked at return to government assistance. Applying survival analysis on data from a national government assistance programme in Singapore, we found two important factors of welfare return to which activation programmes need to pay greater attention. First, return was more likely if former beneficiaries accumulated a higher number of types of arrears rather than higher dollar values of arrears. This new finding contributes to the emerging literature on bandwidth tax, and suggests the importance of designing programmes that relieve mental accounting due to debt and poverty. Second, return was more likely if respondents had an infant or toddler child. This points to the importance of a range of support policies including affordable and accessible childcare, exemption from work requirement in receipt of welfare, and family leave for low-wage workers.